Patient and caregiver benefit‐risk preferences for nonmetastatic castration‐resistant prostate cancer treatment. (29th July 2020) - Srinivas, Sandy; Mohamed, Ateesha F.; Appukkuttan, Sreevalsa; Botteman, Marc; Ng, Xinyi; Joshi, Namita; Tsai, Jui‐Hua; Fang, Jarjieh; Waldeck, A. Reginald; Simmons, Stacey J.
Abstract: Background: Recently approved second‐generation androgen receptor inhibitors (SGARIs) for non‐metastatic castration‐resistant prostate cancer (nmCRPC) have similar efficacy but differ in safety profiles. We used a discrete choice experiment (DCE) to examine how nmCRPC patients and caregivers perceive the benefits versus risks of these new treatments. Methods: An online DCE survey with 14 treatment choice questions was administered to nmCRPC patients and caregivers. Each choice question compared two hypothetical medication profiles varying in terms of 5 safety attributes (risk or severity of adverse events [AEs]: fatigue, skin rash, cognitive problems, serious fall, and serious fracture) and two efficacy attributes (duration of overall survival [OS] and time to pain progression). Random parameters logit models were used to estimate each attribute's relative importance. We also estimated the amounts of OS that respondents were willing to forego for a reduction in AEs. Results: In total, 143 nmCRPC patients and 149 caregivers viewed the AEs in following order of importance (most to least): serious fracture, serious fall, cognitive problems, fatigue, and skin rash. On average, patients were willing to trade 5.8 and 4.0 months of OS to reduce the risk of serious fracture and fall, respectively, from 3% to 0%; caregivers were willing to trade 6.6 and 5.4 months of OS. Conclusions: nmCRPC patients and caregivers preferred treatments with lower AE burdens and were willing to forego OS to reduce the risk and severity of AEs. Our results highlight the importance of carefully balancing risks and benefits when selecting treatments in this relatively asymptomatic population. Abstract : Nonmetastatic castration‐resistant prostate cancer patients and caregivers preferred treatments with lower adverse event (AE) burden and were willing to forego survival to reduce the risks and severity of AEs. They viewed AEs in following order of importance (most to least): serious fracture, serious fall, cognitive problems, fatigue, and skin rash. It is important to carefully balance the risks and benefits when selecting treatments in this relatively asymptomatic population, especially given the differing AE profiles of newer treatments.